Balivaishva Yagya: Significance And Importance in Daily Life - Harsika Jaisawal (Interdisciplinary Journal of Yagya Research, 2022)
Gayatri and Yagya have a unique position and constitute the foundation of the Vedic Culture. Rishis gave concepts of Gayatri and Yagya to practice in daily life to refine animal instincts to divine personalities with the purpose of universal welfare. For this, one of the methods given by Rishis in Vedic time was Balivaishva Yagya. Vedic scriptures described elaborately the practice of it in daily life. The present study aimed to explore the meaning, philosophy, procedure, and utility of Balivaishva Yagya in the present time. ‘Balivaishva Dev’ Yagya is defined as a divine offering for the welfare of the universe. The five offerings of Balivaishva Yagya is represented as Panch Maha (Five Great) Yagya i.e. Brahma-Yagya, Dev-Yagya, Rishi-Yagya, Nar-Yagya, and Bhoot-Yagya. Respectively, they symbolized for 1) inspiration of the self-knowledge of Brahman, 2) progression from animal instincts to divine qualities, 3) having a compassionate life for the upliftment of the backward, 4) creation of environment and social order according to human dignity, 5) extension of intimacy to all living beings including even vegetation. Thus, practicing these five principles through Balivaishva Yagya in the family can help in obtaining harmony in the family by creating a spiritual environment. The five inspirations and messages are hidden in Balivaishva Yagya can create a spiritual environment in the family as well as to solve all the problems of the individual and the world – opening door to all-rounded progress by uprising divine culture in society.